Analisis Tingkat Kesiapan Implementasi Sistem Informasi Kinerja Pegawai Pemerintah Kabupaten Belu - Payong, Yohanes; Abr Lenggu, Max; Verini Beni, Konrardus; J.I Leuhoe, Yeremias (CV. Shofanah Media Berkah, 2023)
The Belu District Government has implemented the Employee Performance Information System (SiKaP) application for civil servants in Belu District. The success of the information system implementation will affect the readiness level of the employees. This research aims to determine the readiness level of the SiKaP application implementation plan. There are three variables in this study, which are independent variables: ICT Infrastructure Readiness and ICT Literacy of employees, while the dependent variable is the readiness of the SiKaP application implementation plan. This research method uses statistical approaches including Validity Test, Reliability Test, Classic Assumption Test (Normality, Multicollinearity), T-Test, F-Test, and Determination Coefficient. Based on the validity and reliability tests, all questionnaire items are considered valid and reliable. Meanwhile, based on the normality test, the distribution is normal with a probability value (sig) of Kolmogorov-Smirnov 2.587 > 0.05. The Multicollinearity test results show a Variance Inflation Factor (VIF) value of 1.205 for the ICT Readiness and ICT Literacy variables (which is less than 10). The Tolerance value for the ICT Readiness and ICT Literacy variables is 0.830 (greater than 10), indicating that the independent variables are free from multicollinearity. The t-test results show that there is an influence of the ICT readiness level of civil servants on the implementation plan of the SiKaP application in Belu District. Similarly, the ICT literacy level of civil servants in Belu District also has an influence. Based on the F-test, there is an influence of the ICT readiness of civil servants (variable x1) and the ICT literacy readiness (variable x2) of civil servants simultaneously on the variable (dependent) readiness of the implementation of the SiKaP application in Belu District (variable y). Based on the readiness levels, they are categorized into five levels, ranging from level 1 to level 5. The ICT Infrastructure Readiness level is at level 4 with a readiness score of 2.096 or 73.77%. The ICT Literacy Readiness level of civil servants in Belu District is at level 4 with a readiness score of 2.226 or 78.51%. The ICT Literacy Readiness level of civil servants in Belu District is also at level 4 with a readiness score of 2.226 or 78.51%.